Investigations of surface interactions and deposition mechanisms in plasma enhanced chemical vapor deposition of silicon-based materials - McCurdy, Patrick R., author; Fisher, Ellen R., advisor (Colorado State University. Libraries, 1999)
Plasma processing of silicon-based materials is widely used in the semiconductor industry for the production integrated circuits. Two very important materials are silicon carbide and silicon nitride. Silicon carbide has found applications in solar cells, flat panel displays, photoreceptors, and photoresist materials, while silicon nitride thin films are used as gate dielectrics and barrier coatings in microelectronic devices, as capacitors in dynamic random access memory cells and in the microfabrication of sensors and actuators. Here the various aspects of the chemistry of plasmas used for producing thin films of hydrogenated amorphous silicon carbide (a-Si1-xCx:H) and hydrogenated amorphous silicon nitride (a-SiNx:H) have been investigated. First, the surface reactivities of two species, NH2 and SiH have been investigated using the imaging of radicals interacting with surfaces (IRIS) technique. IRIS combines spatially-resolved laser-induced fluorescence with molecular beam and plasma techniques. The interaction of NH2 radicals on a variety of substrates has been measured using both NH3 and SiH4/NH3 plasmas. The latter system deposits a-SiNx:H films. Surface production NH2 was found under most plasma conditions. In addition to surface reactivities, the internal and translational energies of NH2 radicals in an NH3 plasma molecular beam have been characterized. The surface reactivity of the SiH radical in SiH4-based plasmas under wide ranging conditions has been measured. Under all deposition conditions, the reactivity of SiH remains high, 0.95 ± 0.05. In addition, velocity distributions for SiH provide translational temperatures under a variety of plasma processing conditions. Second, equivalently powered, pulsed and continuous wave SiH4/CH4 radiofrequency discharges (13.56 MHz) were used to deposit a-Si1-xCx:H. Deposited films were analyzed with FTIR, XPS, SEM, profilometery, and OES. Deposition parameters investigated included pulsed plasma power, duty cycle, substrate bias, and addition of H, as a diluent gas. Oxidation rates for a-Si1-xCx:H films deposited from both pulsed and CW films have been measured using FTIR.
Keywords: materials science; chemical engineering; electrical engineering